Forty percent of Colombian rice producers cultivating 275,608 hectares adopt improved rice varieties developed by CCAFS/Alliance and Rice Growers’ Federation with Ministry of Agriculture support - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Since 2013, CCAFS/Alliance Bioversity-CIAT collaborated with the Colombian Ministry of Agriculture and Rice Growers Federation through the AclimateColombia program to increase farmers’ resilience to climate change and climate variability while improving productivity. An ex-post assessment demonstrated that improved rice varieties developed during program implementation were adopted by 40% (6,424) of in total 16,060 rice farmers. 57% (9,154 farmers) used agroclimatic forecasts to manage their crop. Program technical assistance led to an average rice yield increase of 0.6 tons per hectare.